Institutional Racial Representation and Equity Gaps in College Graduation. (16th April 2022) - Bowman, Nicholas A.; Denson, Nida
ABSTRACT: College graduation rates for racially minoritized students are adversely affected by structural barriers and hostile campus racial climates, which lead to notable equity gaps within and across institutions. Theory and prior literature suggest that the representation of racially minoritized students and instructors may play a role in shaping these disparities, but the evidence to date is limited and has yielded divergent findings. Therefore, the present study directly explored the link between the representation of several minoritized racial groups and equity gaps in six-year graduation rates. The results indicate that same-race representation and the representation of students and instructors from other racially minoritized groups were associated with greater racial equity in graduation outcomes; in fact, no Black-White and Latinx-White gaps were present when Black or Latinx students, respectively, comprised at least half of undergraduates at that institution. Moreover, these patterns occurred predominantly at institutions with virtually no fully online students, which suggests the importance of face-to-face interactions that facilitate situational racial cues and interpersonal experiences that may foster success for racially minoritized students.